The use of indigenous materials in the standardization of ice cream-on-a stick - Miravite, Leonard S.
The utilization of indigenous materials in the production of ice cream on a stick was undertaken. Phase I dealt with the optimization of the ratio of milk-solid and fat to coconut milk. The result of the sensory test showed that the most favorable ratio is 25% milk-solid and fat to 75% coconut milk. In Phase II the optimum level of cassava starch as an alternative stabilizer was determined. The 3% cassava starch met the characteristics of a desirable ice cream on a stick. Standardization of the best formulation in Phase III through sensory test showed that the ice cream was moderately acceptable. The color was neither too light nor too dark, the sweetness was just right, flavor quality was rated slightly characteristic chocolate flavor, flavor strength, creaminess and meltabilty was just right and the texture was smooth. Phase IV dealt with the physico-chemical, microbiological and cost analysis of the standardized product. The fat content is 9%, total solids is 38.48%, melted sample is 9.7 ml, percent overrun is 10.96 and the color is 5YR 6/4. Cost analysis showed that the cost per stick of the ice cream is P1.58.